AB0500 A significant number of patients with rheumatoid arthritis receive low doses of biological agents in clinical practice. (23rd January 2014) - Rosario, V.; Hernández, M.V.; Inciarte-Mundo, J.; Ruiz-Esquide, V.; Cabrera, S.; Gόmez, M.E.; Gόmez-Puerta, J.A.; Ramírez, J.; Cañete, J.D.; Sanmartí, R.
Abstract : Background: The dosages of biological agents used to treat rheumatoid arthritis (RA) have been established by randomized clinical trials. However, lower dosages of these agents may be prescribed in clinical practice in patients with a good response, resulting in reduced costs Objectives: To analyze the frequency and characteristics of a dosage reduction strategy for biological therapies in a cohort of patients with RA attended by the rheumatology department of a tertiary hospital Methods: Cross-sectional study, including all consecutive patients with a diagnosis of RA (1987 ACR criteria), attended by one investigator from June 2011 to November 2011, that had received at least east one dose of a biologic agent in 2011. Data analyzed were: demographic characteristics; disease duration; disease activity measured by the DAS28-ESR; serum CRP; rheumatoid factor (RF) and anti-CCP2; DMARD therapy; dosage, type and duration of biological agent used; time on reduced dosage and reason for dosage reduction. The reduced dosage was defined as a lower dosage than recommended in the manufacturer's technical specification for each product and was not based on a structured protocol. Results: We included 96 patients (87.5% female) with RA with a mean age of 56.1±12.7 years and a mean disease duration of 14.3±8.5 years. RF and/or antiCCP2 were positive in 82.6% of the patients, 71.9% received concomitant therapy with DMARDs and 29.2% had received one or more previous biologic agent. Mean duration of current biologic therapy was 40.3±34.8 months. The biological agents used were TNF antagonists in 66 patients and non anti-TNF (abatacept, rituximab and tocilizumab) in 30 patients. At the time of analysis 38 patients (39.5%) received low dosages of biologicals (52.6% of etanercept patients, 23.7% adalimumab patients and 23.7% of tocilizumab patients). The most-commonly low dosage used was 50 mg every 10-15 days for etanercept, 40 mg every 3 weeks for adalimumab and 6 mg every 4 weeks for tocilizumab. The reason for dosage reduction was remission in 34 patients (89.4%) and low disease activity in 4 (10.6%). The mean time of dosage reduction was 11.4±11.5 months. At the time of analysis, the mean DAS28-ESR and CRP in patients with reduced doses were lower than those of patients without dosage reduction (2.57 vs. 3.47, p=0.09) and (0.37 vs 1.09, p=0.007), respectively), with higher remission rates (76.3% vs 30.7%, p<0.001). The medical decision at the time of the data collection was to keep 92.1% of patients (35 of the 38 patients with dosage reduction) on low doses of biological treatment. Conclusions: In our clinical practice, 40% of patients with RA treated with biological agents received low doses of these drugs, maintaining remission or low disease activity in most cases. Disclosure of Interest: None Declared